Reproductive and larval biology of the sub-Antarctic hermit crab Pagurus comptus reared in the laboratory - Lovrich, Gustavo Alejandro (2006)
Fecundity, hatching rhythm, and the planktotrophic larval development of the hermit crab Pagurus comptus from sub-Antarctic waters of the Beagle Channel (Tierra del Fuego) were studied under controlled laboratory conditions of temperature, light cycle, food supply, and salinity. Fecundity was low, ranging from 134 to 848 eggs per female (cephalotoraxic shield length, SL, 2.3-5.0 mm). Hatching observed in the laboratory ranged from 6 to 30 d. The larval development was studied in laboratory cultures fed with Artemia sp. nauplii and kept at constant 7.0±0.5°C. Larvae invariably passed through four zoeal instars and one megalopa stage. Mean durations of the zoeal stages I to IV were 14.3±1.8, 16.7±4.6, 23.2±6.5, 33.4±9.2 d, respectively. Combined with the 43.8±5.6 d recorded for the survived megalopae, we suggest that the complete larval development lasts about four months. Starved larvae, on average, survived for 22±8.1 d (maximum 38 d) by far exceeding the zoea I duration in fed larvae, but did not reach the moult to the zoea II stage. Unlike other sub-Antarctic decapods, which show a tendency towards abbreviated or endotrophic larval developments at high latitudes, hermit crabs, at their southernmost distributional limit on Earth, show an extended and fully planktotrophic larval development and thus need to synchronize larval release with short periods of high primary production.